PERBEDAAN PENURUNAN PLAK SKOR SETELAH MENGUNYAH BUAH SEMANGKA (CITRULLUS LANATUS) DENGAN BUAH MELON (CUCUMIS MELO L.) PADA SISWA KELAS VIII SMPN 2 KARANG INTAN KABUPATEN BANJAR MARTAPURA - Vivi Aristi Setiani; Danan Danan; Bunga Nurwati (JURNAL TERAPIS GIGI DAN MULUT, 2021)
Plaque occurs when food that contains carbohydrates left in the teeth, therefore plaque control can be done by mechanical methods, namely by chewing fresh, fibrous and water-containing fruit because the fruit is good food for dental health and can be used for natural teeth cleaning. This study aims to determine the difference in decreasing plaque scores after chewing watermelon (citrullus lanatus) with melons (cucumis melo l.) In class VIII students of SMPN 2 Karang Intan, Banjar Martapura Regency. This research is a quasi-experimental research type with the research design used in this study is One Group Pretest-Postest. the sampling technique in this study is total sampling. Sampling is the overall population studied is 60 students. The results showed the average plaque score before chewing watermelon 2.98, and after 1.22 while the average plaque score before chewing melon 3.01 and after 1.66. Based on the results of statistical analysis using the Independent T-Test, p = 0.006 <α = 0.05. Keywords: Watermelon, Melon, Score plaque